Study on the Chemistry and Antimicrobial Activity of Psychotria reevesii Wall. (Rubiaceae) - Giang, Phan Minh; Son, Ha Viet; Son, Phan Tong (Vietnam Journal of Chemistry, 2014)
The first chemical investigation on Vietnamese medicinal plant Psychotria reevesii Wall. (Rubiaceae) led to the isolation and structural determination of β-sitosterol and stigmasterol as a mixture, 1-octacosene, and asperglaucide from n-hexane- and CHCl3-soluble fractions of MeOH extract from the aerial parts of P. reevesii. Phytochemical screening based on color reactions, HPLC analysis, and NMR spectroscopy revealed the concentration of condensed tannins in EtOAc- and n-BuOH soluble fractions. The high accumulation of tannins may be responsible for the antibacterial activities of the polar fractions against Staphylococcus aureus, Pseudomonas aeruginosa, Shigella sonnei, and Shigella flexneri. However, they did not exhibit any inhibitory effect against Escherichia coli, Candida albicans, and Candida stellatoides. Keywords: Psychotria reevesii; Rubiaceae; asperglaucide; antibacterial activity; antifungal activity.